Digitalized Disputes for Online Dispute Resolution and their Legal Basis - Bakhramova, Mokhinur (Research Parks Publishing LLC, 2022)
The jurisdiction of online dispute resolution may involve the application of the conflict of laws rule to the server location or registration of the corresponding domain. If it is a company, then the place of registration is that of the company. It is ideal if the arbitrаtion centre associated with the ODR platform uses its jurisdiction and the approval of the decision by the centre itself to ensure its execution. ODR can gain the most popularity and r elevance within the framework of smart contracts. In this regard, it is necessary to adopt an intеrnаtionаl convention or amend the New York Convention as well as recognise national laws and the UNCITRAL Model Law, a rule on the recognition and enforcement of ODR awards. Also, online аrbitrаtion needs to be described, the procedure is only online, and there are parties and arbitrators in it. In digital аrbitrаtion, everything is done by a computer and through artificial intelligence.